Indigénat et Nouvelle-Calédonie - Gwénael Murphy (Cahiers d’histoire.)
This article presents the review of L’Indigénat. Genèses dans l’empire français. Pratiques en Nouvelle-Calédonie. This substantial and rigorous work, talking about a complex subject, is written by Isabelle Merle and Adrian Muckle, eminent specialists in the colonial history of Oceania. While in France opinion seems to prevail over reflection and critical thinking, the authors suggest a fine analysis of the indigénat. This « exception in law », which makes ordinary something arbitrary, falls at the same time under the history of law, the political history and more particularly under the social history.